PENGGUNAAN GAYA BAHASA DALAM ANTOLOGI CERPEN â€œCERMIN WAKTUâ€ KARYA MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA 2011 FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI PADANG - Afifah, Ummi; Thahar, Harris Effendi; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTThe purpose of this research is to describe the type of language style based on sentence structure and based on whether or not the meaning and function of the language style contained in the anthology of the â€œCermin Waktuâ€ short story by Indonesian Language and Literature Education Students 2011 Faculty of Language and Art, State University of Padang. The method used is descriptive. The approach in this research is the stylistic. Based on the research conducted the type of language style based on sentence structure found 4 types of language style, namely climax, anticlimax, repetition, and antithesis. The type of language style is based on whether or not direct meaning is of two kinds, namely rhetoricalÂ  and the style of figurative language. The rhetorical style of the language is found in 7 types of language styles, namely apostrophes, asindenton, polisindenton, euphemism, pleonasm, rhetorical questions, and hyperbole. The figurative language style is found in 4 types of language styles, namely equality, metaphor, personification, and cynicism and sarcasm. The language style function contained in the anthology of the â€œCermin Waktuâ€ short story is found in 5 types of language style function, namely concreting 25 speeches, asserting 88 utterances, beautifying 24 speeches, smoothing 2 speeches, and insinuating 4 speeches. Â Kata Kunci: Gaya bahasa, Fungsi, Jenis